2020
DOI: 10.1002/eqe.3263
|View full text |Cite
|
Sign up to set email alerts
|

Mainshock‐consistent ground motion record selection for aftershock sequences

Abstract: In recent years, the additional risk posed to the built environment due to aftershock sequences and triggered events has been brought to attention, and several efforts have been directed towards developing fragility functions for structures in damaged conditions. Despite this rise of interest, a rather fundamental component for such tasks, namely that of aftershock ground motion record selection, has remained under-scrutinized. Herein, we propose a pragmatic procedure that can be applied for the selection of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 50 publications
(98 reference statements)
2
32
0
Order By: Relevance
“…However, most of these studies (i.e., Raghunandan et al 2015; Burton and Sharma 2017) apply the developed artificial MS-AS sequences in conjunction with the IDA approach, implying excessive scaling on the records and related issues (e.g., Miano et al 2018). More recently, Papadopoulos et al (2020) developed an advanced strategy combining spectrally compatible ground motions into MS-AS sequences that are representative of potential rupture scenarios, by implementing the appropriate triggering mechanisms and recently-developed MS-AS spectral acceleration correlation models.…”
Section: Ground-motion Selection and Randomized Sequence Assemblingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these studies (i.e., Raghunandan et al 2015; Burton and Sharma 2017) apply the developed artificial MS-AS sequences in conjunction with the IDA approach, implying excessive scaling on the records and related issues (e.g., Miano et al 2018). More recently, Papadopoulos et al (2020) developed an advanced strategy combining spectrally compatible ground motions into MS-AS sequences that are representative of potential rupture scenarios, by implementing the appropriate triggering mechanisms and recently-developed MS-AS spectral acceleration correlation models.…”
Section: Ground-motion Selection and Randomized Sequence Assemblingmentioning
confidence: 99%
“…The authors showed that the median values of aftershock fragility curves are reduced by 14-46% compared to the undamaged state and the reduction is much more significant when the initial mainshock DS is large. Some studies have also focused on different aspects such as MS-AS record/sequence selection, with special focus on hazard consistency (e.g., Goda 2015;Papadopoulos et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This approach does not require a site‐specific, hazard‐consistent record selection (e.g. Papadopoulos et al 3 …”
Section: Introductionmentioning
confidence: 99%
“…state-dependent fragility). Most studies derive seismic fragility in terms of maximum interstorey drift thresholds [3][4][5] , although in some cases this is considered in conjunction with the residual drift 6 . This may create inconsistencies in the resulting statistical models due to inappropriate consideration of damage accumulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation